2022
DOI: 10.52380/ijpes.2022.9.4.920
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Pre-Service Mathematics Teachers’ Techno-Pedagogical Content Knowledge regarding Geometry

Abstract: Despite the significance of incorporating technology into geometry instruction, many teachers still find it difficult to teach geometry using technology. This study employed a techno- pedagogical content knowledge (TPACK) survey of 70 pre-service mathematics teachers (29 males, 41 females) from a public university. The goal was to determine which domains, if any, were open for development so that a course could be designed to meet these needs. The data was analysed thematically according to the TPACK sub-domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…The findings of this study underscore the effectiveness of the RETA model in positively influencing the STEM attitudes of senior-grade pre-service teachers. As seen in other topics, the integration of Realistic, Exploratory, Technology-enhanced, and Active principles in lesson planning in fractions and integers contributed to a perceptible shift in participants' perceptions and beliefs regarding STEM education (Renkl, 2011;Saralar-Aras & Tiflis, 2020). This study revealed that providing training that encourages pre-service teachers to use these resources in courses created with appropriate technology-enhanced mathematics resources positively impacted their attitudes towards the STEM approach.…”
Section: Discussionmentioning
confidence: 68%
“…The findings of this study underscore the effectiveness of the RETA model in positively influencing the STEM attitudes of senior-grade pre-service teachers. As seen in other topics, the integration of Realistic, Exploratory, Technology-enhanced, and Active principles in lesson planning in fractions and integers contributed to a perceptible shift in participants' perceptions and beliefs regarding STEM education (Renkl, 2011;Saralar-Aras & Tiflis, 2020). This study revealed that providing training that encourages pre-service teachers to use these resources in courses created with appropriate technology-enhanced mathematics resources positively impacted their attitudes towards the STEM approach.…”
Section: Discussionmentioning
confidence: 68%
“…Teacher knowledge is essential in classroom instruction (Saralar, 2016). Kurt (2019), as cited in Shulman's, classifies teacher knowledge into content, general pedagogy, curriculum, pedagogical content knowledge, awareness of learners, understanding of academic settings, and educational objectives, goals, and moral standards.…”
Section: Tpack Frameworkmentioning
confidence: 99%